Addicts Who Survived : An Oral History of Narcotic Use in America before 1965 - Courtwright, David T., 1952-; Des Jarlais, Don, 1945-; Joseph, Herman, 1931- (Book collections on Project MUSE., 1989)
The authors employ the techniques of oral history to penetrate the nether world of the drug user, giving readers a portrait of life in the drug subculture during the "classic" era of strict narcotic control.